Roof Fracture Characteristics and Strata Behavior Law of Super Large Mining Working Faces - Guozhen Zhao; Baisheng Zhang; Lihong Zhang; Chao Liu; Shuai Wang (Geofluids)
Exploiting the working face in coal mines using a super long mining length and large mining height has become important for intensive production with high yield and high efficiency. The paper develops a roof structure model to analyze the influence of 195 m, 242.4 m, and 376 m working face lengths at large mining height in Wangzhuang Coal Mine in China as the case study. The roof fracture characteristics, migration law, and strata behavior law under different working face lengths are compared and studied by numerical simulation, and the reliability of support selection in the working face at large mining height is analyzed by field measurement statistics. The results show that the roof fracture mode of a super large working face is a successive layered fracture. The length of the working face has little effect on the roof fracture step length, and the fracture step length is positively correlated with the thickness of the rock stratum. The roof subsidence law for a super large working face is different from the intermittent subsidence of the unimodal Gaussian distribution curve of ordinary working faces, which shows the intermittent subsidence of multiple ordinary working faces. The roof periodic weighting of a super large working face, which fluctuates violently within 100 m at both ends, is more drastic than that of an ordinary working face as a whole. Field statistical analysis shows it is more appropriate to choose high-strength support for a super large working face.